BESARAN EFFECT SIZE PROGRESSIVE MUSCLE RELAXATION PADA PENURUNAN TEKANAN DARAH PENDERITA HIPERTENSI - Susanto, Rachmat (STIKes Bina Cipta Husada, 2024)
Many complementary therapies can be applied to lower blood pressure in people with hypertension, including relaxation therapy. Progressive Muscle Relaxation (PMR) is a relaxation therapy that is often used to lower blood pressure. However, how big the effect size is is not yet known. The effect size is important to measure to see how big the difference or the significance of the effect of an intervention to make it more effective and precise in its beneficiaries. This study aims to identify how big the effect size of Progressive Muscle Relaxation is on blood pressure as measured on Cohen's scale. The research method used was True Experiment Design with the Pre Test-Postest Control Group Design type with the number of respondents in the intervention group and the control group each being 30 respondents with hypertension. Data were analyzed by statistical analysis of the Mean Difference Test of Two Unpaired Groups. The results of the study in the PMR group obtained an effect size of 0.06 compared to the normal breathing group with an effect size of 0.01. Conclusions PMR has a moderate effect size in lowering blood pressure.